(untitled) (Research, Society and Development, 2021)
Background: SARS-CoV-2 is the infectious agent responsible for COVID-19, its transmission occurs through the release of respiratory droplets and aerosols. Aim: Identify the main characteristics of SARS-CoV-2 aerosols dispersion in indoor air. Methods: Scoping Review was conducted using the databases: National Library of Medicines – MEDLINE/Pubmed, Scopus, Web of Science, Virtual Health Library (VHL) and Cochrane Library, the search in gray literature was performed on Google Scholar, OpenGrey and Grey Literature Report, from March to September 2020. The descriptors used were "coronavirus" and "aerosol". Data were selected and screened following the protocol established by the The Joanna Briggs Institute, PRISMA flow diagram and EndNote reference management tool. Findings: Ten papers were selected, which presented characteristics that could influence the SARS-CoV-2 aerosols dispersion, with highlight to: aerosol origin; viral load identified in the air (2.86 copies/liter of air); aerosol particle size with viral load (0.25 μm); dispersion (10.00 m); air stay time (3 h); influence of air temperature and relative humidity. Conclusion: Aerosol particles containing SARS-CoV-2 may have infectious viral charge, presenting a minimum size up to 0.25 μm, being able to reach up to 10 m of distance and survive in the air for a few hours. The variables air temperature and relative humidity did not present consistent evidence to influence the dispersion of SARS-CoV-2 aerosols.